2009
DOI: 10.1186/1471-2458-9-57
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a community-based program for prevention and control of non-communicable disease in a developing country: The Isfahan Healthy Heart Program, Iran

Abstract: BackgroundCardiovascular diseases are the most common cause of mortality in Iran. A six-year, comprehensive, integrated community-based demonstration study entitled Isfahan Healthy Heart Program (IHHP) conducted in Iran, and it started in 2000. Evaluation and monitoring are integrated parts of this quasi-experimental trial, and consists of process, as well as short and long-term impact evaluations. This paper presents the design of the "process evaluation" for IHHP, and the results pertaining to some intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
(9 reference statements)
0
22
0
Order By: Relevance
“…Therefore, it can be concluded that WIP, as a practical tool for health promotion among factory and office workers in their worksites, creates tangible changes in people's lifestyle which not only ensures healthy workers, but also leads to a healthy societycells 9, 1113. The results of this study which are indicative of relative reducing in negative surface charge of LDL particle in the presence of CRP, are in line with the results of a study conducted by Rufail et al It is noteworthy that in that study, the result of electrophoresis was obtained only after 2 hours of incubation, but in the present study, this period was extended to 18 hours 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be concluded that WIP, as a practical tool for health promotion among factory and office workers in their worksites, creates tangible changes in people's lifestyle which not only ensures healthy workers, but also leads to a healthy societycells 9, 1113. The results of this study which are indicative of relative reducing in negative surface charge of LDL particle in the presence of CRP, are in line with the results of a study conducted by Rufail et al It is noteworthy that in that study, the result of electrophoresis was obtained only after 2 hours of incubation, but in the present study, this period was extended to 18 hours 19.…”
Section: Discussionmentioning
confidence: 99%
“…In both phases, Pars Azmoon kits (Iran) were used to measure serum lipids and Biosystems for blood sugars. IHHP's execution facts were completely explained elsewhere 10, 11…”
Section: Methodsmentioning
confidence: 99%
“…For cardiovascular disease as a whole, some large studies have been reported, mostly positive [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], although longer term translation of findings into actual clinical care within those systems is unknown.…”
Section: Monitoring Patients Status and Response To Treatmentmentioning
confidence: 99%
“…It is a quasi-experimental trial that includes a reference area and several levels of evaluation including process, impact and outcome evaluations. IHHP involves individual, community and environmental changes to support health behaviour modification 2021…”
Section: Introductionmentioning
confidence: 99%